The changing earth: Exploring geology and evolution - James Stewart Monroe (West, 1994)
This book provides students an understanding of the principles and processes of geology and how geology relates to the human experience; that is, how geology effects not only individuals, but society in general.Three interrelated themes run through the preceding discussion: Plate tectonics; Orrganic evolution; geologic time